2007
DOI: 10.1002/tl.264
|View full text |Cite
|
Sign up to set email alerts
|

Engaging differences: Self‐Authorship and the decision‐making process

Abstract: Decisions that involve consideration of inconsistent or contradictory information provide a context for understanding and supporting intellectual development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
0
8
0
3
Order By: Relevance
“…In the third phase, Becoming the Author of One's Own Life, individuals are expected to construct their own internal perspectives about knowledge (Epistemological), about themselves (Intrapersonal), and about the nature of their relationships with others (Interpersonal) (Baxter Magolda, 2001). When individuals reach these third and fourth phases, they are considered self-authored (Laughlin & Creamer, 2007;Pizzolato, 2005Pizzolato, , 2006Pizzolato, , 2007. In this fourth and final phase, Internal Foundations, individuals are observed as having acted 'in ways that integrated the intrapersonal and cognitive in interpersonal arenas' (Pizzolato, 2007, p. 32).…”
Section: Self-authorship Dimensions and Phasesmentioning
confidence: 99%
“…In the third phase, Becoming the Author of One's Own Life, individuals are expected to construct their own internal perspectives about knowledge (Epistemological), about themselves (Intrapersonal), and about the nature of their relationships with others (Interpersonal) (Baxter Magolda, 2001). When individuals reach these third and fourth phases, they are considered self-authored (Laughlin & Creamer, 2007;Pizzolato, 2005Pizzolato, , 2006Pizzolato, , 2007. In this fourth and final phase, Internal Foundations, individuals are observed as having acted 'in ways that integrated the intrapersonal and cognitive in interpersonal arenas' (Pizzolato, 2007, p. 32).…”
Section: Self-authorship Dimensions and Phasesmentioning
confidence: 99%
“…Three themes emerged: students' sources of information, their decision-making process, and their resulting feelings. Because these components are closely linked to the three aspects of self-authorship described by Laughlin and Creamer (2007) we utilized their terminology in our analysis (see also Baxter Magolda, 1998).…”
Section: Course Withdrawalmentioning
confidence: 99%
“…In reviewing the interviews with the aim of discovering how students make their course withdrawal decisions, we found that students engaged in an elementary decision-making process. Based on the iterative analysis, we organized the students' comments about their decision process via three components of self-authorship outlined by Laughlin and Creamer (2007): students' sources of information when considering a decision, the management of this information in their decisionmaking process, and the affective and behavioral impact of the resulting decision.…”
Section: Interviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pizzolato (2010) noted the challenge posed by the fact that some items can be similarly endorsed by respondents at different phases of self-evolution and concluded that "qualitative methods may seem like the best option for self-authorship research" (p. 201), assuming that interview approaches invite participants to discuss meaning making in ways that illuminate cross-cultural variations. Elizabeth Creamer and Anne Laughlin (2005) and Laughlin and Creamer (2007) found that their self-authorship questionnaire provided information about whom students consulted for career decisions rather than how they constructed their consultations, the latter information emerging in interviews. Aware of the assessment challenges recounted here and in the interest of providing a psychometrically sound measure for assessing educational practice to promote self-authorship, Creamer continued work on the Career Decision Making Survey, which includes Likert-type items keyed to External Formulas, Crossroads, and early Self-Authoring (Creamer, Baxter Magolda, and Yue, 2010).…”
Section: Assessment Formatsmentioning
confidence: 99%